1996
DOI: 10.1097/00006123-199601000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Injuries Involving the Transverse Atlantal Ligament: Classification and Treatment Guidelines Based upon Experience with 39 Injuries

Abstract: Comprehensive anatomic and clinical analyses of 39 patients with injuries involving the transverse atlantal ligament or its osseous insertions were performed to assess the morphology of the injured ligaments and the patients' capacity to heal. Injuries of the upper cervical spine were screened with plain radiographs, thin-section computed tomography, and magnetic resonance imaging studies. The injuries were classified as disruptions of the substance of the ligament (Type I injuries, n = 16) or as fractures and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
143
0
9

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(155 citation statements)
references
References 18 publications
3
143
0
9
Order By: Relevance
“…The integrity of the TAL is the most important factor in determining the method of treatment. 6,13 Spence et al 14 reported a lateral mass spread >6.9 mm implied a disruption of the TAL. More recently, it has been proposed that MRI is a more sensitive indicator of TAL disruption than the ''rule of Spence.''…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The integrity of the TAL is the most important factor in determining the method of treatment. 6,13 Spence et al 14 reported a lateral mass spread >6.9 mm implied a disruption of the TAL. More recently, it has been proposed that MRI is a more sensitive indicator of TAL disruption than the ''rule of Spence.''…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] There is a high prevalence of concomitant fractures of the second cervical vertebra. 4,5 The unstable Jefferson fracture of C1 is a C1 burst fracture with concomitant injury of the transverse atlantal ligament.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dickman et al [2,3] classified transverse ligament injuries into two main types, which have two distinctly different treatment outcomes. Type I injuries are intrasubstance ruptures of the transverse ligament that are incapable of healing and because of instability are believed by most to require surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The American Academy of Neurological Surgeons recommends that the rigid collar be used to reduce the cervical injury for the first 4 weeks and, if unsuccessful, immobilization should be continued [18]. Both Dickman et al [19] and Lo et al [20] showed that a cervical orthosis collar or halo device can be successfully used for AAI induced by the transverse atlantal ligament. When considering perioperative complications, many authors also recommend conservative management in patients with Down syndrome and for asymptomatic patients with AAI [21,22].…”
Section: Discussionmentioning
confidence: 99%